Intervention Programs to Control Vitamin A Deficiency in Asia - A Review - Sri Raharjo (Indonesian Association of Food Technologists, 1994)
Existing prevalence data suggest that vitamin A deficiency among children still represents a major problem in developing Asian countries including Indonesia, Bangladesh, India, Philippines, and Thailand. Plasma retinol is the most common assessment method for determining vitamin A status. The severity stages of xerophthalmia, along with their characteristics, are used frequently to follow clicinal signs of vitamin A deficiency. Massive dosing of 200,000 IU of vitamin A (60 mg ratinol equivalent) every six months interval or fortification of vitamin A on food items have been done for the period of 12 to 24 months. The result were decreased in the risk of night blindness, incidence of keratomalacia and Bitot’s spots, and lower mortality rate.